P092 Circulating classical monocytes and intestinal macrophages exhibit reduced response to IL-10 in IBD. (25th January 2019) - Hoti, I; McCarthy, N; Giles, E; Ayada, I; Harrow, P; Gordon, H; Stagg, A; Lindsay, J
Abstract: Background: Mice in which the IL-10 receptor (IL-10R) is knocked out in macrophages (Mφs) alone develop bacterially driven colitis, demonstrating that IL-10 mediated control of these cells is essential to prevent intestinal inflammation. Humans who have loss-of-function IL-10R mutations develop severe early-onset IBD; these individuals may represent the end of a spectrum in which suboptimal control of Mφs by IL-10 leads to gut inflammation. Our aim was to investigate whether monocytes and monocyte-derived intestinal Mφs from adult-onset IBD patients exhibit a diminished response to IL-10. Methods: Blood monocyte subsets (CD14++CD16− classical; CD14++CD16+ intermediate; CD14+CD16++ non-classical) and monocyte-derived intestinal Mφs in IBD patients and controls were identified by flow cytometry. Inhibition of LPS-induced TNFα production by IL-10 was measured by intracellular cytokine staining. Results: LPS-induced TNFα production by classical monocytes (78 ± 4.46% TNFα+) was significantly ( p < 0.001) inhibited by IL-10 in healthy controls. A similar frequency (89 ± 2.39%) of intermediate monocytes produced TNFα. However, compared with classical monocytes, this response was significantly ( p = 0.009) less well controlled by IL-10 despite higher IL-10R expression and similar IL-10-induced STAT3 phosphorylation. Fewer LPS-stimulated non-classical monocytes produced TNFα (33 ± 6.24%; p < 0.001), which was poorly inhibited by IL-10 due to poor IL-10-induced STAT3 phosphorylation as a consequence of low STAT3 availability. IL-10 was significantly less effective at inhibiting TNFα production by classical monocytes from IBD patients than from controls ( p = 0.026) (Figure 1), despite increased expression of IL-10Rα and IL-10-induced STAT3 phosphorylation. The implications of a suboptimal response to IL-10 in classical monocytes was investigated in CD14+ monocyte-derived Mφs in the intestine. Two populations of CD45+HLA-DRhi cells were identified based on CD14 expression: CD14hi (P1) and CD14lo (P2). Both populations spontaneously produced TNFα, which was enhanced with LPS stimulation. Inhibition of LPS-induced TNFα by IL-10 was reduced in IBD patients compared with controls. Conclusions: TNFα production by intermediate and non-classical monocytes is poorly controlled by IL-10 and these populations may contribute to inflammation in the IL-10-rich intestine. A lower responsive to IL-10 observed in both classical monocytes and monocyte-derived intestinal Mφs from IBD patients and may contribute to inflammation.